Revitalisasi Semangat Nasionalisme dan Patriotisme Generasi Z Melalui Nilai-Nilai Pancasila - Seriyanti Seriyanti (IKIP Budi Utomo Malang, 2022)
Nationalism and Patriotism are manifestations of awareness as part of a nation that is willing to sacrifice for the prosperity and glory of the nation, potentially or actually together to achieve, maintain and perpetuate the identity, integrity, prosperity and strength of the nation, through the spirit of nationalism. This study aims to revitalize the spirit of nationalism and patritism Gen Z through Pancasila values. By using the literature study method, the researcher analyzed several references relevant to the topic of discussion in this study, internet media through virtual workshop activities. The results of the study can be concluded that. Gen Z needs to be given education through Pancasila education to revitalize the spirit of nationalism and patriotism.